A Eu3+/Gd3+-EDTA-doped structurally controllable hollow mesoporous carbon for improving the oral bioavailability of insoluble drugs and in vivo tracing. (23rd June 2016) - Liu, Jia; Zhao, Yating; Cui, Yu; Yue, Yang; Gao, Yikun; Zhao, Qinfu; Liu, Jie; Wang, Siling
Abstract: A structurally controllable fluorescence-labeled hollow mesoporous carbon (HMC) was simply prepared to improve the oral bioavailability of insoluble drugs and further trace their delivery process in vivo . The hollow structure was derived from an inverse replica process using mesoporous silica as a template and the fluorescent label was prepared by doping the carboxylated HMC with a confinement of Eu 3+ /Gd 3+ -EDTA. The physicochemical properties of the composites were systematically characterized by transmission electron microscopy, Fourier transform infrared spectroscopy and photoluminescence spectra tests prior to studying their effects on drug-release behavior and biodistribution. As a result, the thickness of the carrier's shell was adjusted from 70 nm to 130 nm and the maximum drug loading was up to 73.6%. The model drug carvedilol (CAR) showed sustained release behavior compared to CAR commercial capsules, and the dissolution rate slowed down as the shells got thicker. AUC0-48h and Tmax were enlarged 2.2 and 6.5 fold, respectively, which demonstrated that oral bioavailability was successfully improved. Bioimaging tests showed that the novel carbon vehicle had a long residence time in the gastrointestinal tract. In short, the newly designed HMC is a promising drug carrier for both oral bioavailability improvement and in vivo tracing.